2009
DOI: 10.1007/s00467-009-1240-8
|View full text |Cite
|
Sign up to set email alerts
|

ACE gene insertion/deletion polymorphism and renal scarring in children with urinary tract infections

Abstract: Urinary tract infection is a common bacterial disease that presents during childhood and may lead to renal scarring. Several studies have shown a strong association between the angiotensin converting enzyme (ACE) deletion polymorphism and renal scarring in children with vesicoureteric reflux (VUR). The purpose of this study was to investigate the possible correlation between the ACE deletion polymorphism and renal scarring in 186 children with urinary tract infection (UTI), of whom 90 were renal scar positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…The study of the TGF-β1 (509)C > T polymorphism was performed by three groups in Korea, Egypt, and Poland, respectively [32,42,43]. The study of the ACE DD genotype was performed by four groups; three showed a OR>1 (two from Turkey [40,46] and one from the island of Crete [50]) and the fourth study showed an OR in the opposite direction (northern Greece [51]). It could be argued that the strong heterogeneity among the studies may be due to unknown geographic and/or socioeconomic and perhaps genetic background differences that cannot be evaluated in the meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The study of the TGF-β1 (509)C > T polymorphism was performed by three groups in Korea, Egypt, and Poland, respectively [32,42,43]. The study of the ACE DD genotype was performed by four groups; three showed a OR>1 (two from Turkey [40,46] and one from the island of Crete [50]) and the fourth study showed an OR in the opposite direction (northern Greece [51]). It could be argued that the strong heterogeneity among the studies may be due to unknown geographic and/or socioeconomic and perhaps genetic background differences that cannot be evaluated in the meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Calculation disclosed that seven studies presented a significant deviation from HWE [32,41,42,48,[51][52][53]. In three studies, because of a lack of information, we were not able to calculate the HWE test in populations tested for the angiotensinogen (AGT) [46,47], angiotensin II type 1 receptor (AT1R) [46,47], AT2R [47], plasminogen activation inhibitor type 1 (PAI-1) [46], and tumor necrosis factor alpha (TNF-α) gene polymorphisms [50].…”
Section: Quality Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations